PTH-008 Endoscopic Resection of Large Colorectal Polyps in A UK Tertiary Referral Unit. (17th August 2016) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: Whilst the extensive experience of endoscopic resection of large colorectal polyps in Japan has resulted in clear and consistent indications for various techniques depending on polyp size and morphology, practise in western Europe is less well defined. We report the results of a prospective series of endoscopic resections using a variety of techniques from one of only a few tertiary referral centres in the UK providing advanced interventional endoscopy. The patients in this series present some unique challenges, for example the high proportion of patients referred with deeply scarred lesions after previous failed attempts at resection, and the large mean polyp size. Methods: A prospective series of colorectal endoscopic resections form a tertiary referral centre in the UK. Surveillance endoscopy was performed at 3 months and 12 months after resection. Results: 363 polyps with a mean size of 56 mm were resected in 326 patients who had a mean age of 71 years: 309 by EMR, 38 by ESD and 16 by hybrid procedures involving ESD. The mean follow up was 12.2 months. Almost all patients were referred after their polyps were at least biopsied and 38% of polyps were deeply scarred from previous intervention. Despite this, adenoma recurrence occurred in only 9.7% of patients, 17% of which were diminutive. 6 patients with recurrence required surgery, 2 right hemicolectomies, 1 TEMS and 1 anterior resection and 2 declined surgery. 67% of patients with recurrence were treated successfully endoscopically with no further recurrence. Of those patients without invasive cancer at their first endoscopic resection, 95% were free from recurrence and had avoided surgery at last follow up. There was only one clinically significant perforation. 2 patients were admitted with post-procedure bleeding, 1 managed conservatively and 1 with endoscopic clips. Conclusion: These data demonstrate the effectiveness of a tertiary interventional endoscopy unit in a western setting in treating large and complex colorectal polyps, with low recurrence rates and very few significant complications. In contrast to practise in the east, more education is required to prevent multiple attempted interventions before referral to a highly specialised unit. Disclosure of Interest: None Declared